2020
DOI: 10.1063/1.5139459
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the π* shape resonances of uracil

Abstract: We have investigated the effect of microsolvation on the π* shape resonances of uracil, referred to as π1* and π2* in the order of increasing energy. Our study considered uracil–water aggregates with six solvent molecules obtained from Monte Carlo simulations in the liquid phase. To explore the ensemble statistics, we combined scattering calculations, performed in the static exchange and static exchange plus polarization approximations, with linear regressions of virtual orbital energies to the scattering resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…The definition of a resonance state as pole of the K-matrix, 29 establishes a relation between the local position and width, G L (R) = G(R,E res (R)), which is useful to build complex potential models. 53,54,76 For the p à 2 shape resonance, the linear relation…”
Section: Complex Potential Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of a resonance state as pole of the K-matrix, 29 establishes a relation between the local position and width, G L (R) = G(R,E res (R)), which is useful to build complex potential models. 53,54,76 For the p à 2 shape resonance, the linear relation…”
Section: Complex Potential Modelsmentioning
confidence: 99%
“…It should be clear that the Wigner threshold law is relevant for the entry width, given in eqn (4), but not for the local width, G L , used to compute the autoionization survival probability. 66 For the s à CBr shape resonance, we employed the form G L = E a exp(ÀbE), based on previous studies, 66,76 obtaining The s à CBr state stabilizes as the C 5 Br bond stretches, becoming a bound state for DR CBr = 0.1 Å and 0.2 Å, such that we only used three points to obtain eqn (25), namely DR CBr = À0.2 Å, À0.1 Å and the equilibrium bond length. In addition, the large background in the A 0 symmetry component, arising from the dipolar interaction, 41 increases the uncertanties of the resonance parameters, i.e., the background makes the eigenphase model in eqn (23) more difficult.…”
Section: Complex Potential Modelsmentioning
confidence: 99%
“…Likewise, molecular dynamics simulations have shown that an excess electron localizes very quickly onto nucleobases, within 5–25 fs, such that the water molecules are not able to reorient to form a cavity to solvate the electron. ,, Moreover, this configuration appears to be the most stable configuration for nucleobase anions, as there is no significant reorientation of the water molecules to create a cavity within roughly 1 ps, , and calculations of a uracil molecule paired with a solvated electron show rapid electron transfer to uracil. , In addition, simulations indicate that hydrogen atoms are generally hydrophilic and that solvated electrons in clusters prefer cavities near the cluster surface, , indicating that solvated electrons would likely migrate quickly to more electronegative sites such as nucleobases. While there have been previous computational efforts to study the uracil anion in solution, these efforts have used relatively small unit cells ,, without sufficient water molecules to converge the uracil solvation shell or have employed QM/MM methods which are not ideal to yield accurate solvation structures for neutral or anionic uracil . Furthermore, most studies focused on the ground state only, although some recent work has calculated more than one state. , …”
Section: Introductionmentioning
confidence: 99%
“…While there have been previous computational efforts to study the uracil anion in solution, these efforts have used relatively small unit cells ,, without sufficient water molecules to converge the uracil solvation shell or have employed QM/MM methods which are not ideal to yield accurate solvation structures for neutral or anionic uracil . Furthermore, most studies focused on the ground state only, although some recent work has calculated more than one state. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation